2018
DOI: 10.3389/fimmu.2018.00695
|View full text |Cite
|
Sign up to set email alerts
|

Sparking Fire Under the Skin? Answers From the Association of Complement Genes With Pemphigus Foliaceus

Abstract: Skin blisters of pemphigus foliaceus (PF) present concomitant deposition of autoantibodies and components of the complement system (CS), whose gene polymorphisms are associated with susceptibility to different autoimmune diseases. To investigate these in PF, we evaluated 992 single-nucleotide polymorphisms (SNPs) of 44 CS genes, genotyped through microarray hybridization in 229 PF patients and 194 controls. After excluding SNPs with minor allele frequency <1%, out of Hardy–Weinberg equilibrium in controls or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 108 publications
6
16
0
Order By: Relevance
“…After excluding SNPs with minor allele frequency they found some gene expression (<1%), out of a Hardy‐Weinberg equilibrium in controls or in strong linkage disequilibrium ( r 2 ≥ 0.8); 201 SNPs remained for logistic regression. The authors also reported increased serum levels of complement C3, and C5‐b9 deposition in lesions observed more frequently in the PF and EPF patients in comparison with the normal controls …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…After excluding SNPs with minor allele frequency they found some gene expression (<1%), out of a Hardy‐Weinberg equilibrium in controls or in strong linkage disequilibrium ( r 2 ≥ 0.8); 201 SNPs remained for logistic regression. The authors also reported increased serum levels of complement C3, and C5‐b9 deposition in lesions observed more frequently in the PF and EPF patients in comparison with the normal controls …”
Section: Discussionsupporting
confidence: 88%
“…The authors also reported increased serum levels of complement C3, and C5-b9 deposition in lesions observed more frequently in the PF and EPF patients in comparison with the normal controls. 23 Of interest is the correlation we found between positivity of other autoimmune blistering and skin diseases such lupus, BP, DH, and PV and the positivity of the staining for complement C5-b9 that perfectly matched what we had reported on IHC staining with other immunoglobulins and complement. 24 Indeed, our findings suggest that in these other autoimmune skin diseases, the immune response may also be more complex than the classically described and currently accepted mechanisms.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Even so, this regulatory intergenic SNP was not associated with PF and PV in the Tunisian population (Mejri et al, 2009). In line with this result, C5 polymorphisms were also not associated with FS (Bumiller-Bini et al, 2018).…”
Section: Genetics Sheds Light On the Controversial Relevance Of The Csupporting
confidence: 59%
“…The first genetic associations reported were variants within the human leucocyte antigen ( HLA ) genes, with strong associations with alleles of HLA‐DRB1 and HLA‐DQB1 . Furthermore, our group has demonstrated several other associations of PF with genes involved in immune responses …”
Section: Introductionmentioning
confidence: 91%